RESPONS PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescens L.) TERHADAP PEMBERIAN JAMUR Trichoderma sp. - Ema Oktapia (Indobiosains, 2021)
A research entitled Responses to the Growth of Chili Rawit (Capsicum frutescens L.) to Trichoderma sp Mushroom, March to June 2017 in Muara Siban Village, Lahat Regency, South Sumatra. This study aims to determine the Responses of Rawit Chillies Growth Against Giving Mushroom Trichoderma sp. The method used was Completely Randomized Design (RAL) with 6 treatments and 4 replications with the treatment details of P0 (without Trichoderma sp), P1 (25 g Trichoderma sp / kg soil pellet), P2 (50 g of Trichoderma sp / kg soil pellets ), P3 (75 g of Trichoderma sp / kg soil pellets ),P4 (100 g of Trichoderma sp / kg soil pellets) pellet, P5 (125 g of Trichoderma sp / kg soil pellets), was analyzed by Analysis of Scales Variety (ANSIRA) at 5% . The parameters observed in this study were plant height, stem diameter and number of leaves. The results of the analysis of Sidik Ragam (ANSIRA) showed that Trichoderma sp had significant effect on plant height, stem diameter, and number of leaves. The best treatment was found in the treatment of 75 g of Trichoderma sp / kg soil pellets because it has the highest average value of each parameter ie the average height of plant 25.7 cm, stem diameter 3.22 mm, and the number of leaves 15 strands, while the lowest yield In the treatment without Trichoderma sp pellet sp with an average height of 15.3 cm, stem diameter 2.07 mm, and leaf number 8.75 strands.Keywords: Trichoderma sp, Growth , Chilli Rawit (Capsicum frutescens L.).